Does fiscal and financial green policy coordination curb corporate “greenwashing”? Evidence from the green loan interest subsidies policy in China - Fang, Xubing; Liu, Maotao (Technological and Economic Development of Economy, 2025)
Amidst the push for green development, finding ways to effectively coordinate fiscal and financial policies to curb corporate “greenwashing” has emerged as a crucial issue to investigate. Using data from non-financial listed firms in China from 2011 to 2022, this study employs a multi-period difference-in-differences model, treating the green loan interest subsidies (GLIS) policy as a quasi-natural experiment to examine its impact on “greenwashing”. We find that the GLIS policy significantly suppresses corporate “greenwashing.” GLIS policy not only stimulates bank credit supply and increases the scale of green credit, but also motivates banks to strengthen their risk identification mechanisms, thereby curbing “greenwashing.” The inhibitory effect is more pronounced in firms with high financing constraints, low transparency in environmental management systems, and heavy pollution firms. Moreover, GLIS policy can synergize fiscal and financial policies, addressing the deficiencies of individual policies and enhancing their practical effectiveness in green governance. Overall, our results verify the inhibitory effect of the GLIS policy on “greenwashing,” providing evidence and useful insights for China and other countries or regions to promote coordinated green policies between fiscal and financial sectors.First published online 20 October 2025